Nodular mass in the vaginal dome in a previously hysterectomized woman: A study case - Pinto, Ana; Suárez, Marisa; Scigliano, Horácio (Citotech Online - Case Review, 2017)
Total hysterectomy is a very common surgical technique, that removes the cervix and should eliminate the presence of glandular cells in vaginal smears. However, this fact does not always happen. In this study, it is related the case of a 49-year-old woman, hysterectomized 6 years before, which control vaginal smear presents ciliated cylindrical cells without atypia. The cytological diagnosis was the presence of ciliated cylindrical cells, which, with the clinical information provided, were suggestive of possible tubal prolapse. Subsequent histological study confirmed the suspected cytological diagnosis.